2016
DOI: 10.1121/1.4946898
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of acoustic harmonics generated by nonlinear ultrasound wave propagation in water at various frequencies

Abstract: Ultrasound-based thermometry requires a temperature-sensitive acoustic parameter that can be used to estimate the temperature by tracking changes in that parameter during heating. The objective of this study is to investigate the temperature dependence of acoustic harmonics generated by nonlinear ultrasound wave propagation in water at various pulse transmit frequencies from 1 to 20 MHz. Simulations were conducted using an expanded form of the Khokhlov-Zabolotskaya-Kuznetsov nonlinear acoustic wave propagation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…The authors claim that the nonlinear parameter can be effectively used in order to estimate the temperature in tissue medium. Temperature dependence of harmonics in different frequency ranges is reported in [28]. In this study the opposite dependency of nonlinear parameter to the temperature is detected in frequency ranges of 1, 3.3 MHz and 13, 20MHz.…”
Section: Active Thermometrymentioning
confidence: 48%
“…The authors claim that the nonlinear parameter can be effectively used in order to estimate the temperature in tissue medium. Temperature dependence of harmonics in different frequency ranges is reported in [28]. In this study the opposite dependency of nonlinear parameter to the temperature is detected in frequency ranges of 1, 3.3 MHz and 13, 20MHz.…”
Section: Active Thermometrymentioning
confidence: 48%
“…The ambient temperature has an influence on the wave propagation in a component. Since this also has an impact on the formation of the harmonic frequencies [37], the experiments were carried out at constant temperature. The experimental setup is shown in Figure 9.…”
Section: Experimental Validationmentioning
confidence: 99%
“…Simulations were performed to study the temperature dependence of the harmonic's amplitude in a lossless medium in transmit mode for a plane wave of finite amplitude [29]. Maraghechi et al studied the temperature dependence of harmonics' amplitudes and their ratios in water at several frequencies and showed that harmonics are monotonically increasing functions of temperature at 13 MHz [30].…”
Section: Introductionmentioning
confidence: 99%